Cross‐correlating soil aggregate stability methods to facilitate universal interpretation - Deborah Aller; Joseph P. Amsili; Harold M. vanEs (Agricultural & Environmental Letters)
Abstract Aggregate stability is a critical physical indicator of soil health. However, multiple methods are used for measuring aggregate stability, making it difficult to compare results and limiting universal interpretations in soil health assessment frameworks like Soil Health Assessment Protocol and Evaluation. We cross‐correlated three common water‐stable aggregate methods (WSACASH, WSAARS, and WSASLAKES) using a dataset of nearly 1400 samples and developed pedotransfer functions using random forest models to evaluate method performance. We found that the WSAARS and WSACASH methods can be reasonably cross correlated through pedotransfer functions because they use similar processes for estimating aggregate strength. Conversely, the WSAARS and WSASLAKES methods are not transferable. We suggest that the WSAARS aggregate stability method is the most established and best reference method for use in soil health analysis frameworks. Interpretation consistency will lead to more robust comparisons of aggregate stability as a key physical soil health indicator. Core Ideas Different approaches for measuring aggregate stability prevent generalized result interpretation. The water‐stable aggregate wet sieve procedure (WSAARS) is proposed as the reference method for interpretation. Other soil aggregate stability methods can be variably correlated with WSAARS.